Golgi Alkalinization by the Papillomavirus E5 Oncoprotein - Schapiro, Florencia (The Rockefeller University Press, 2000)
The E5 oncoprotein of bovine papillomavirus type I is a small, hydrophobic polypeptide localized predominantly in the Golgi complex. E5-mediated transformation is often associated with activation of the PDGF receptor (PDGF-R). However, some E5 mutants fail to induce PDGF-R phosphorylation yet retain transforming activity, suggesting an additional mechanism of action. Since E5 also interacts with the 16-kD pore-forming subunit of the vacuolar H(+)-ATPase (V-ATPase), the oncoprotein could conceivably interfere with the pH homeostasis of the Golgi complex. A pH-sensitive, fluorescent bacterial toxin was used to label this organelle and Golgi pH (pH(G)) was measured by ratio imaging. Whereas pH(G) of untreated cells was acidic (6.5), no acidification was detected in E5-transfected cells (pH ∼7.0). The Golgi buffering power and the rate of H(+) leakage were found to be comparable in control and transfected cells. Instead, the E5-induced pH differential was attributed to impairment of V-ATPase activity, even though the amount of ATPase present in the Golgi complex was unaltered. Mutations that abolished binding of E5 to the 16-kD subunit or that targeted the oncoprotein to the endoplasmic reticulum abrogated Golgi alkalinization and cellular transformation. Moreover, transformation-competent E5 mutants that were defective for PDGF-R activation alkalinized the Golgi lumen. Neither transformation by sis nor src, two oncoproteins in the PDGF-R signaling pathway, affected pH(G). We conclude that alkalinization of the Golgi complex represents a new biological activity of the E5 oncoprotein that correlates with cellular transformation.